2015
DOI: 10.4049/jimmunol.1303163
|View full text |Cite
|
Sign up to set email alerts
|

Deficiency of Antigen-Specific B Cells Results in Decreased Trypanosoma cruzi Systemic but Not Mucosal Immunity Due to CD8 T Cell Exhaustion

Abstract: Vaccines against mucosally invasive, intracellular pathogens must induce a myriad of immune responses in order to provide optimal mucosal and systemic protection, including CD4+ T cells, CD8+ T cells and antibody-producing B cells. In general, CD4+ T cells are known to provide important helper functions for both CD8+ T cell and B cell responses. However, the relative importance of CD4+ T cells, CD8+ T cells and B cells for mucosal protection is less clearly defined. We have studied these questions in detail us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
42
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(43 citation statements)
references
References 41 publications
1
42
0
Order By: Relevance
“…In mice exposed to a highly virulent challenge, PD-1 expression and/or other signs of T cell exhaustion are evident (27, 28). Such high dose and acutely lethal infections are also associated with other immunological anomalies (29).…”
Section: Immune Exhaustion During Chronic T Cruzi Infectionmentioning
confidence: 99%
“…In mice exposed to a highly virulent challenge, PD-1 expression and/or other signs of T cell exhaustion are evident (27, 28). Such high dose and acutely lethal infections are also associated with other immunological anomalies (29).…”
Section: Immune Exhaustion During Chronic T Cruzi Infectionmentioning
confidence: 99%
“…This Th1-driven immune response is the most protective against T. cruzi infection, as previously demonstrated. 36,41,42 In addition, the critical importance of specific antibody-producing B cells for controlling systemic T. cruzi infection was recently reported by Sullivan et al 43 The robust humoral immune response and intense cellular response observed would explain the decreased parasitemia found in mice treated with the combination of both plasmids. These results become even more important since serum levels of enzymes that are markers of muscle damage in chronic Chagas disease (CK, AST and LDH) achieved significantly lower activity levels with respect to controls.…”
Section: Discussionmentioning
confidence: 81%
“…A second dose of anti-CD20 was administered at 2 wk after i.n. AdHu5Ag85Avaccination for the maintenance of B cell depletion (7,8,37,38). This B cell depletion regimen effectively wiped out B cells in the lymph nodes, peripheral blood, and lung before vaccination (data not shown) as verified by immunostaining for CD19 and B220 surface markers expressed on developing and mature B cells.…”
Section: Respiratory Mucosal Adhu5ag85a Vaccination Induces Ag85a-spementioning
confidence: 99%